2009
DOI: 10.1007/s00239-009-9205-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Molecular Evolution of Guanine Deaminases: From Guanine to Dendrites

Abstract: Guanine deaminase (GDA; guanase) is a ubiquitous enzyme that catalyzes the first step of purine metabolism by hydrolytic deamination of guanine, resulting in the production of xanthine. This hydrolase subfamily member plays an essential role in maintaining homeostasis of cellular triphosphate nucleotides for energy, signal transduction pathways, and nitrogen sources. In mammals, GDA protein levels can play a role in neuronal development by regulating dendritic arborization. We previously demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…This is consistent with previous microarray reports that GDA was up-regulated by 3.087-fold in melasma skin lesions [9]. GDA is a ubiquitous enzyme that mediates the initial step of purine metabolism by the hydrolytic deamination of guanine, thus being involved in the synthesis of xanthine and tyrosine metabolism [28]. It is known that mammalian GDA plays a role in regulating dendritic arborization, thus being involved in neuronal development [29].…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with previous microarray reports that GDA was up-regulated by 3.087-fold in melasma skin lesions [9]. GDA is a ubiquitous enzyme that mediates the initial step of purine metabolism by the hydrolytic deamination of guanine, thus being involved in the synthesis of xanthine and tyrosine metabolism [28]. It is known that mammalian GDA plays a role in regulating dendritic arborization, thus being involved in neuronal development [29].…”
Section: Discussionsupporting
confidence: 81%
“…These conclusions are backed up by a phylogenetic analysis clearly separating the GDA and GSDA subfamilies and assigning the C. elegans and G. sulphuraria sequences to the GDA group ( Figure 5). Up to now, GDA of the cytidine/deoxycytidylate deaminase type has been documented only in prokaryotes (Fernández et al, 2009). …”
Section: Gsda Is Unique To Plantsmentioning
confidence: 99%
“…By contrast, GDA genes are well known, and the corresponding activity occurs in many organisms (Yuan et al, 1999;Maynes et al, 2000;Nygaard et al, 2000). There are two evolutionary origins for GDA (Nygaard et al, 2000;Fernández et al, 2009). The majority of species, including human and Escherichia coli, employ a protein that is member of the amidohydrolase family (Pfam profile PF01979), while a few prokaryotic organisms, including Bacillus subtilis, possess a protein belonging to the cytidine/deoxycytidylate deaminase family (Pfam profile PF00383).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis of K. pneumoniae GuaD using a BLAST search showed that this protein has 86% identity with the proposed guanine deaminase of K. oxytoca and 58% identity with E. coli GuaD. The sequence includes the motif PGF VDAHVH between positions 73 and 81, which matches the consensus sequence implicated in metal binding (Zn 2ϩ ) in prokaryotic proteins of the cyclic amidohydrolase family (12). This motif is also present in K. oxytoca GuaD (28).…”
Section: Resultsmentioning
confidence: 85%